Tinjauan Hukum Islam Terhadap Putusan Cerai Gugat Beralasan Suami Terpidana Penjara - Habibi, Ahmad; Maulana, Bintan; Irfan, Hidayad; Arifin, Zainul; Muhaini, Akhmad (Universitas Cokroaminoto Yogyakarta, 2024)
This in-conreto legal research delves deeper into the legal basis determined by the Panel of Judges in deciding on a divorce lawsuit because the husband is a convict. The research takes a case that has been determined in one of the Religious Courts in the Special Region of Yogyakarta number 0909/ Pdt.G/2011/PA.BTL (0909). The results are then discussed in more depth according to Islamic law. Through the exploration of the rules of fiqh and the proposals of fiqh as well as interviews with several judges, it can be interpreted that the judge's decision has referred to the interests needed in the family by avoiding the risks that may arise due to the father/husband being sentenced to prison for several years. In the review of Islamic law, the judge has fulfilled the rules of fiqh and followed the fatwa of the agreed-upon fiqh school of thought.